The Effect of Online Project-Based Learning Application on Mathematics Students' Visual Thinking Continuum in Covid-19 Pandemic - Wahyuningsih, Sapti; Qohar, Abd.; Satyananda, Darmawan; Atan, Noor Azean (International Journal of Interactive Mobile Technologies (iJIM), 2021)
The COVID-19 pandemic led to the implementation of the Work From Home (WFH) policy. The impact of this policy is to replace the process of teaching and learning activities by using an online learning system. In this industrial era 4.0, the integration of web applications is very much needed in problem-solving learning. One that can be used to integrate web applications in learning through project-based learning. The focus of this research is to study the effects of online project-based learning applications on mathematics students' visual thinking continuum. Instruments used in the form of rubric virtual mind maps, audio-visual and virtual posters are used to observe students' visual thinking continuum. The instrument was analyzed with the Rasch measurement model software named WINSTEPS. This study used one group pretest-posttest design to see the effect of integrating web applications in learning through project-based learning analyzed using SPSS. The results of instrument analysis for rubric virtual mind maps, audio-visual products, and virtual posters on measure person obtained good person reliability, MNSQ infit, and MNSQ OUTFIT the average rating is very good. For the ZSTD infit and the ZSTD outfit, the average value is close to 0.0 so that the quality of the person's reliability is good. The results of the conformity quality of the items with the model studied from the fit order items obtained the value of Outfit mean square (MNSQ), Outfit Z-standard (ZSTD), and the value of Point Measure Correlation (Pt Mean Corr) for the three instruments met good criteria. The results of the analysis of paired samples test from 54 respondents obtained p <0.05 so that the base learning project has the effect of increasing students' visual thinking continuum. Implementation of online project-based learning in mathematics learning is an alternative that can be used to improve students' creative problem-solving skills in online learning